(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The adolescents in age group of 10–19 years constitute 21.4% of the Indian population. Adolescents are basically considered a healthy group and mostly ignored in mortality surveys conducted by Government agencies and NGOs. The leading cause of mortality among youth in the world is injuries (75%) including motor vehicle injuries. In India, suicide is the second leading cause of death in this group. Adolescent deaths and social aetiology of these untimely mortalities have been studied in both the developing as well as developed countries of the world indicating varying trends. Rohtak is a city located in NCR of India which has experienced a large influx of people from rural areas in recent times. This has resulted in exposure and adjustment-related social problems in the youth leading to their increased mortality. This prospective study was planned at General Hospital Rohtak to estimate the total number of autopsies performed in the second decade of life and analyse and correlate the cause of death with socio-demographic profile of the deceased individuals.